The atmospheric boundary layer above the Agulhas current - Lee-Thorp, Andrew Michael (Department of Oceanography, 2016)
This thesis describes the atmospheric boundary layer above the Agulhas Current using shipboard meteorological measurements and rawinsonde ascents. The juxtaposition of the warm Agulhas Current and cool shelf waters is shown to have far-reaching effects on the overlying atmosphere. Air-sea fluxes of momentum, sensible and latent heat and resultant boundary layer characteristics demonstrate high horizontal inhomogeneity. The results suggest that this inhomogeneity is permanent. The spatial heat flux gradient is reflected in the overlying atmosphere by a transition in stability of the boundary layer and potential cumulus formation from the cool shelf to the warm current. For airflow perpendicular to the Agulhas Current an internal boundary layer was observed to develop at the inshore sea surface temperature front. Onshore-moving air accumulated a significant quantity of moisture during its trajectory over the current. When airflow is parallel to the current an atmospheric moisture front exists along the axis of the inshore sea surface temperature front. The mean thermodynamic structure of the atmosphere was investigated. An inversion capped the boundary layer whilst a second, higher-level subsidence inversion was found which acts to limit the vertical development of cumulus clouds and therefore the redistribution of heat and moisture above the boundary layer. The results presented in this thesis are useful in two ways. The Agulhas Current has frequently been linked to South African climate. This is the first dedicated study which quantifies and characterizes the atmospheric boundary layer in this region. Secondly, maritime airmasses are dramatically modified above the Agulhas Current. The resultant large horizontal inhomogeneity, its vertical extent and permanence suggest that its inclusion is vital to any successful climate model. Atmospheric general circulation models have been criticized for not taking into account regions of strong horizontal inhomogeneity. The results of this thesis support this argument and highlight the need for similar studies. Bibliography: pages 116-123.